2011
DOI: 10.1021/es103150v
|View full text |Cite
|
Sign up to set email alerts
|

Bioaugmentation and Adsorption Treatment of Coking Wastewater Containing Pyridine and Quinoline Using Zeolite-Biological Aerated Filters

Abstract: Bioaugmented zeolite-biological aerated filters (Z-BAFs), i.e. adding isolated degrading bacteria into the BAFs with zeolite as fillings, were designed to treat coking wastewater containing high concentrations of pyridine and quinoline and to explore the bacterial community of biofilm on the zeolite surface. The investigation was carried out for 91 days of column operation and the treatment of pyridine, quinoline, total organic carbon (TOC), and ammonium was shown to be highly efficient by bioaugmentation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(63 citation statements)
references
References 34 publications
1
60
1
Order By: Relevance
“…Most bioaugmentation studies on wastewater have revealed that the inoculated strain(s) may significantly alter indigenous microbial community composition (Bai et al, 2011;Shi et al, 2015;Wang et al, 2009;Zhu et al, 2015). In our study, however, the indigenous microbial community maintained their predominant structure after the introduction of strain QJX1.…”
Section: Impact Of Bioaugmentation On Microbial Community In the Sandcontrasting
confidence: 55%
“…Most bioaugmentation studies on wastewater have revealed that the inoculated strain(s) may significantly alter indigenous microbial community composition (Bai et al, 2011;Shi et al, 2015;Wang et al, 2009;Zhu et al, 2015). In our study, however, the indigenous microbial community maintained their predominant structure after the introduction of strain QJX1.…”
Section: Impact Of Bioaugmentation On Microbial Community In the Sandcontrasting
confidence: 55%
“…Limitation on the study of PAHs in coking wastewater can be ascribed to many factors, including: (1) distribution of coking plants mainly in developing countries, which limits the study of representative wastewater samples; (b) economic and social conditions that do not allow developing countries to fully address pollutants from coking wastewater; and (c) technically difficult collection, extraction, and separation of target organic compounds from the complex matrix (Busetti et al 2006;Poster et al 2006). As economic development has proceeded and public health awareness has increased, recent research has begun to focus on coking wastewater (Zhu et al 2009;Bai et al 2011;Chu et al 2012). In recent years, many efforts have been made to develop effective analytical techniques for PAHs in complex matrices (Chen et al 2005;Busetti et al 2006;Guo et al 2007), which make the identification and quantitative analyses possible for PAHs in coking wastewater.…”
Section: Responsible Editor: Leif Kronbergmentioning
confidence: 99%
“…Illumina MiSeq high throughput sequencing technology was performed to reveal the relative abundance and diversity of microbiology in these two parallel systems. Since coking wastewater is usually regarded as an extreme environment with high toxicity and refractoriness, the microorganisms involved should be quite different from those in domestic wastewater [5]. But the microbial community which is responsible for the cooking wastewater treatment process is still significantly different?…”
Section: Mini Reviewmentioning
confidence: 99%